Global, regional, and national epidemiology of allergic diseases in children from 1990 to 2021: findings from the Global Burden of Disease Study 2021 - Jun Zheng; Yi-jing Jin; Cheng-hai Wang; Chu Feng; Xin-yuan Lai; Shu-qing Hua; Jia-hui Tai (BMC Pulmonary Medicine)
Abstract Background Asthma and atopic dermatitis (AD) represent significant global health challenges in children. This study aimed to investigate trends in incidence, prevalence, and disability-adjusted life years (DALYs) for childhood asthma and AD from 1990 to 2021. Methods The study utilized information from the Global Burden of Disease (GBD), Injuries, and Risk Factors Study 2021. The sample size for this study consisted of children with asthma or AD between the ages of 0 and 14. From 1990–2021, we calculated asthma and AD’s age-standardized incidence, prevalence, and DALYs by area, age, sex, and socio-demographic index. Results In 2021, global childhood asthma prevalence reached 95.7 million cases (age-standardized rate: 4,758 per 100,000), with the Low SDI region recording 25.4 million cases. For AD, global prevalence was 72.4 million cases (age-standardized rate: 3,600 per 100,000), predominantly in Middle SDI regions (19.7 million cases). Between 1990 and 2021, age-standardized incidence rates decreased for both conditions. Geographic variations were notable: High-income North America showed the highest asthma incidence, while Western Europe led in AD prevalence. The global burden of asthma-related DALYs declined from 6.9 million in 1990 to 4.6 million in 2021, with significant regional disparities. Conclusions Despite decreasing age-standardized rates, childhood asthma and AD continue to pose substantial health burdens globally, with marked variations across regions and socioeconomic strata. These findings emphasize the need for targeted, region-specific interventions.